Spatial Features Encoded in the Preverbs of Zan Languages Group - Gersamia, Rusudan ("Intercultural Dialogues" Transactions, 2021)
Preverb in Zan language groups (Megrelian and Laz languages) is a principal prefix which, in combination with verb roots and stems referring to dynamicity and stativity (in association with other functional elements), is involved in organizing of space, and by means of which we establish spatial relations.Similarly to other Kartvelian languages, spatial features, encoded in the Zan preverb, in fact describe a direction (landmark, path) of movement of a subject (figure) of motion and its relation with other im/mobile objects in space (person, thing). As different from simple ones, Zan derived preverbs provide information about topological or landscape features of a place; therefore, we refer to them as locative, while to simple ones – as orienting. In Zan preverbs, encoded spatial categories reveal according to individual kinds: path /trajectory + orientation (vertical and horizontal) path + deixis/reference (egocentric orientation) Verbal spatial categories reveal in a combined way within a preverb; therefore, they can be assumed as models made up of these categories as of simple values; for instance, for dynamic verbs: path + orientation + subject deixis/referent absolute path + orientation + personal deixis/referent variable non-targeted motion without a referent For stative verbs: location + subject deixis/referent Owing to their function, derived preverbs encode locative and landscape features of an area (place), making the semantic structures of derived preverbs much more complicated.